Ischemic Preconditioning for Off-Pump Isolated Coronary Artery Bypass Grafting - N. Ioffe; S. Salo; M. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2020)
National Amosov Institute of Cardiovascular Surgery is a pioneer in implementation of coronary artery bypass grafting (CABG) in our country [1]. Since 2000, over 13,000 off-pump CABG operations were performed in our clinic [2]. At the same time, reperfusion syndrome, which develops during the formation of distal anastomoses and in the postoperative period, can induce intraoperative heart failure and life-threatening arrhythmias [3], despite the fact that off-pump CABG has a number of advantages versus on-pump. Damage to the myocardium, accompanied by an increase in the level of troponin after surgery, leads to deterioration in the patients [4]. That is why the use of pre- and postcodification techniques during off-pump CABG is an important component of successful surgical intervention. The literature describes many methods of ischemic and pharmacological pre- and postconditioning, but their mechanisms have not yet been fully understood [5]. Ischemic preconditioning (PreC) is an increase in myocardial resistance to ischemia-reperfusion that results from the pre-exposure to short-term ischemia and is expressed through intracellular mechanisms. Our study included 52 cases of off-pump coronary artery bypass grafting (OPCABG). The subjects were divided into 2 groups. The patients of group 1 underwent ischemic PreC before surgical intervention. In group 2, no preoperative PreC was performed. Hemodynamic parameters were analyzed in all the subjects during the surgical intervention.